PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF GOOGLE SLIDES PADA MATERI PENGGOLONGAN HEWAN BERDASARKAN JENIS MAKANANNYA - Afandi, Kevin; Hendracipta, Nana; Yandari, Indhira Asih Vivi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
This research aims to develop interactive learning media based on Google Slides on material on classifying animals based on type of food and to determine the feasibility of interactive learning media based on Google Slides on material on classifying animals based on type of food. The research was conducted in class V-C at SDN Petir 4, Tangerang City with a total of 40 students. The method used is R&D (research and development) with the 4D research model (define, design, development, disseminate) developed by Thiagarajan. The average percentage obtained from material experts I and II was 91.67% with a very reasonable interpretation. The average percentage obtained from media experts I and II was 90.67% with a very reasonable interpretation. The student response questionnaire obtained an average of 93% with a very decent interpretation. Based on the percentage of research results that have been mentioned, it can be concluded that this research has produced an interactive learning media product based on Google Slides which contains material on classifying animals based on their type of food with categories that are very suitable for use in learning activities in class V elementary schools.